Provider Perspectives on Factors Affecting the PrEP Care Continuum Among Black Cisgender Women in the Midwest United States: Applying the Consolidated Framework for Implementation Research. (1st July 2022) - Johnson, Amy K.; Pyra, Maria; Devlin, Samantha; Uvin, A. Ziggy; Irby, Shemeka; Blum, Cori; Stewart, Eric; Masinter, Lisa; Haider, Sadia; Hirschhorn, Lisa R.; Ridgway, Jessica P.
Abstract : Background: To End the HIV Epidemic and reduce the number of incident HIV infections in the United States by 90%, pre-exposure prophylaxis (PrEP) uptake and persistence among cisgender women, particularly racial and ethnic minority women, must be increased. Medical providers play a pivotal role across the PrEP care continuum. Methods: In this qualitative study, guided by the Consolidated Framework for Implementation Research, we explored health care provider perspectives on facilitators and barriers to PrEP implementation strategies for Black cisgender women in the Midwest United States. Data were analyzed using a deductive thematic content analysis approach. Results: A total of 10 medical providers completed individual qualitative interviews. Using the Consolidated Framework for Implementation Research framework, we identified intervention characteristics (cost, dosing, and adherence), individual patient and provider level factors (self-efficacy, knowledge, and attitudes), and systematic barriers (inner setting and outer setting) that ultimately lead to PrEP inequalities. Implementation strategies to improve the PrEP care continuum identified include provider training, electronic medical record optimization, routine patient education, and PrEP navigation. Conclusion: This study provides (1) medical provider insight into implementation factors that can be modified to improve the PrEP care continuum for Black cisgender women and (2) an implementation research logic model to guide future studies.